Operational efficacy and its relation to the business strategy - Salinas , Javie (2020)
Long term vision development is an important feature of strategic planning. Short term vision is more related to urgent problem solving, which can devia- te the corporate management attention. Operative efficacy seeks to connect short- and long-term activities and gives sustainability to the strategy. Future profitability of companies depends on coherence between operative efficacy and strategic efficacy.